SUSCEPTIBILITY AND TOLERANCE TO ROOT-KNOT NEMATODES (MELOIDOGYNE INCOGNITA) OF TELFAIRIA OCCIDENTALIS UNDER ORGANIC CONVERSION - Atungwu, Jonathan; Olabinjo, O. O.; Eche, C. O.; Tijjani, I. (FUDMA JOURNAL OF SCIENCES, 2020)
Three cultivars of Telfairia occidentalis were assessed for their resistance or otherwise to root-knot nematodes (Meloidogyne spp.) infection on the field. Seeds were extracted from the pods of the selected cultivars and planted on moist sawdust in nursery trays to raise seedlings for transplanting. The experiment was laid out in Randomized Complete Block Design and replicated thrice. Pre-plant soil samples were taken to estimate initial nematode populations. At seven days after transplanting, eggs of Meloidogyne incognita (Mi) were extracted from 60 day-old Celosia argentea and used for inoculation of the three cultivars of T. occidentalis at approximately 5000 eggs/stand. Plants were, thereafter, observed for vine length, vine girth and number of leaves from two weeks till 8 weeks after transplanting. Final soil nematode population and root gall indices were determined at 60-66 days after inoculation. Reproduction factor was determined and used along with the gall indices to rate the cultivars for resistance or susceptibility to Mi. Results showed that cultivars NHTo-020 and NHTo-030 were susceptible to root-knot nematode which implied that plants allowed nematode reproduction and also suffered yield loss while cultivar NHTo-010 was tolerant to nematode infestation meaning that nematode reproduction took place but the plant does not suffer yield loss. There was no significant (P>0.05) difference in the mean vine length and number of leaf irrespective of the inoculum while effect on the vine girth was significantly variable. The inoculated plants gave significantly better vegetative growth than the naturally infested plants which indicated genetic variability in the cultivars.